5-fluorouracil loaded magnetic cellulose bionanocomposites for potential colorectal cancer treatment - Yusefi, Mostafa; Soon, M. L. K.; Shameli, Kamyar; Teow, Sin Yeang *; Ali, Roshafima Rasit; Siew, K. K.; Chan, H. Y.; Wong, Magdelyn Mei Theing *; Lim, Wei Ling *; Kuča, K. (Elsevier, 2021)
Magnetic polymer nanocomposites are inherently multifunctional and harbor assorted physiochemical actions for applications thereof as novel drug nanocarriers. Herein, Fe3O4-nanoparticles were supported on rice straw cellulose for 5-Fluorouracil carrier abbreviated as MC/5-FU for potential colorectal cancer treatments. Several analyses indicated the multifunctional properties of MC/5-FU bionanocomposites. Transmission and scanning electron microscopy study demonstrated that Fe3O4 nanofillers covered the cellulose matrix. The drug release from MC/5-FU was evaluated under various pH and temperature conditions, showing the maximum release at pH 7.4 and 44.2 °C. In in vitro anticancer assay, MC/5-FU exhibited enhanced selectivity and anticancer actions against 2D monolayer and 3D tumour spheroid models colorectal cancer cells. The anticancer effects of MC/5-FU with magnetic targeting and heat induction were also examined. This easily synthesized MC/5-FU indicated the potential in application as a low-cost drug formulation for colorectal cancer treatments.